Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) production from biodiesel by-product and propionic acid by mutant strains of Pandoraea sp. - de Paula, Fabrício C. [UNESP]; de Paula, Carolina B. C. [UNESP]; Gomez, José Gregório C.; Steinbüchel, Alexander; Contiero, Jonas [UNESP] (Wiley, 2017)
Pandoraea sp. MA03 wild type strain was subjected to UV mutation to obtain mutants unable to grow on propionic acid (PA) but still able to produce poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] from glycerol and PA at high 3HV yields. In shake flask experiments, mutant prp25 was selected from 52 mutants affected in the propionate metabolism exhibiting a conversion rate of PA into 3HV units of 0.78 g g−1. The use of crude glycerol (CG) plus PA or valeric acid resulted in a copolymer with 3HV contents varying from 21.9 to 30 mol% and 22.2 to 36.7 mol%, respectively. Fed-batch fermentations were performed using CG and PA and reached a 3HV yield of 1.16 g g−1, which is 86% of the maximum theoretical yield. Nitrogen limitation was a key parameter for polymer accumulation reaching up to 63.7% content and 18.1 mol% of 3HV. Henceforth, mutant prp25 is revealed as an additional alternative to minimize costs and support the P(3HB-co-3HV) production from biodiesel by-products. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1077–1084, 2017.
Keywords: biodiesel; biopolymer; glycerol; Pandoraea sp; polyhydroxyalkanoates